Integration of Halal Lifestyle in the Value Chain of Tegal Batik Industry: UMKM Perspective Through Phenomenological Approach - Masrukhan, M.; Salamah, Mar’atus; Faridah, Hidayatul; Hakim, Arif Rohman; Falah, Zidnal (Dinasti Publisher, 2025)
The Tegal batik industry holds significant potential in supporting the halal economy by integrating halal lifestyle principles into its value chain. This study aims to explore the experiences of Tegal batik SMEs in implementing the halal concept, analyze the application of halal principles in the batik industry's value chain, and identify challenges faced in adopting halal practices. Using a qualitative approach with phenomenology and data triangulation, this research examines the perspectives of batik SME actors through in-depth interviews, observations, and document analysis. The findings indicate that adopting halal principles in the Tegal batik industry enhances product competitiveness in both domestic and international markets. However, major challenges include a lack of understanding of halal standards, the cost of certification, and difficulties in accessing global halal markets. Therefore, support from the government and relevant institutions in the form of education, training, and certification subsidies is crucial to accelerating halal lifestyle adoption in the batik industry.